A mathematical model of aerobic methane oxidation coupled to denitrification. Issue 9 (3rd May 2018) - Modin, Oskar
ABSTRACT: Aerobic methanotrophic bacteria use methane as their only source of energy and carbon. They release organic compounds that can serve as electron donors for co-existing denitrifiers. This interaction between methanotrophs and denitrifiers is known to contribute to nitrogen losses in natural environments and has also been exploited by researchers for denitrification of nitrate-contaminated wastewater. The purpose of this study was to develop a mathematical model describing aerobic methane oxidation coupled to denitrification in suspended-growth reactors. The model considered the activities of three microbial groups: aerobic methanotrophs, facultative methylotrophs, and facultative heterotrophs. The model was tested against data from the scientific literature and used to explore the effects of the oxygen mass transfer coefficient, the solids retention time, and the fraction methane in the feed gas on nitrate removal. The fraction of methane in the feed gas was found to be critical for the nitrate removal rate. A value of about 15% in air was optimal. A lower methane fraction led to excess oxygen, which was detrimental for denitrification. A higher fraction led to oxygen-limitation, which restricted the growth rate of methanotrophs in the reactor.